2021
DOI: 10.1371/journal.pone.0256968
|View full text |Cite
|
Sign up to set email alerts
|

A harmful religio-cultural practice (Chhaupadi) during menstruation among adolescent girls in Nepal: Prevalence and policies for eradication

Abstract: Background Chhaupadi is a deeply rooted tradition and a centuries-old harmful religio-cultural practice. Chhaupadi is common in some parts of Karnali and Sudurpaschim Provinces of western Nepal, where women and girls are considered impure, unclean, and untouchable in the menstrual period or immediately following childbirth. In Chhaupadi practice, women and girls are isolated from a range of daily household chores, social events and forbidden from touching other people and objects. Chhaupadi tradition banishes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…The number of participants ranged from 88 to 672 in the surveys. Among the studies using mixed methods (Amatya et al, 2018; Gautam, 2017; Joshi, 2015; Pandit et al, 2021; Parajuli et al, 2018; Thakuri et al, 2021; Thomson et al, 2019), interviews and focus group discussions were used to triangulate the survey. Studies using qualitative methods (Baumann, Merante, et al, 2021; Baumann, Lhaki, et al, 2021; Joshi & Maharjan, 2021; Karki & Khadka, 2019a; Khadka, 2020; Thapa et al, 2019; Wong, 2018) elicited more nuanced information on the underlying phenomena and provided critical, detailed information regarding chhaupadi .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The number of participants ranged from 88 to 672 in the surveys. Among the studies using mixed methods (Amatya et al, 2018; Gautam, 2017; Joshi, 2015; Pandit et al, 2021; Parajuli et al, 2018; Thakuri et al, 2021; Thomson et al, 2019), interviews and focus group discussions were used to triangulate the survey. Studies using qualitative methods (Baumann, Merante, et al, 2021; Baumann, Lhaki, et al, 2021; Joshi & Maharjan, 2021; Karki & Khadka, 2019a; Khadka, 2020; Thapa et al, 2019; Wong, 2018) elicited more nuanced information on the underlying phenomena and provided critical, detailed information regarding chhaupadi .…”
Section: Resultsmentioning
confidence: 99%
“…One participant in Amatya et al (2018) said that if she did not follow chhaupadi , it would bring bad luck and something bad would happen. Thakuri et al (2021) also found that their participants continued the practice because they thought that they were impure during menstruation, were afraid of gods, and worried that family members would get sick.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations